Wavelet Based Medical Image Watermarking Scheme for Patient Information Authenticity - Gökçen Çetinel; Lukman ÇERKEZI (International Journal of Applied Methods in Electronics and Computers, 2016)
Telemedicine is an important technique that permits transmission of medical and imaging data from one place to other, ensures the reliability of data and provides a convenient communications between patient and medical staff. In this study, Discrete Wavelet Transform (DWT) and Singular Value Decomposition (SVD) based medical image watermarking method that hides the patient information into medical image without affecting the image quality is proposed for the purpose of authentication. At the watermark (secret image containing patient information) embedding process, a chaotic map called as Arnold Cat Map (ACM) is applied to the watermark to improve the security of the method.  So that the aim of the proposed watermarking scheme is personal authentication by ensuring the perceptual invisibility, PSNR (Peak Signal-to-Noise Ratio) values are calculated during the simulations. According to the experimental results, we can say that the proposed method provides higher PSNR values than compared current methods. Furthermore, in simulations DWT and SVD based watermarking scheme is implemented as chaotic and non-chaotic watermarking scheme to investigate the effect of chaotic map on the performance of the proposed algorithm.